2003
DOI: 10.1007/s00442-003-1250-3
|View full text |Cite
|
Sign up to set email alerts
|

Are impacts of an exotic predator on a stream food web influenced by disturbance history?

Abstract: Predatory species have been introduced to habitats spanning a wide range of environmental conditions. To better understand the consequences of predation in natural communities we need to examine how variations in abiotic factors modify the influence of predation. The effects of introduced predators may vary amongst habitats if natural disturbance affects the abundance and taxonomic composition of consumers and their resources, or the predator alters recolonisation after disturbance. We tested whether a bed-mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
2
27
2
Order By: Relevance
“…Morphologically, as the catfish grows, both its gape size and number of gill rakes increase, conferring more efficiency to filter feeding (Munro 1967). Therefore the trophic impacts of the catfish may be contrary to those of piscivorous invaders, such as different bass and trout species, that cause significant top-down effects within the invaded communities (Flecker and Townsend 1994;Gratwicke and Marshall 2001;Cambray 2003b;Nystrom and McIntosh 2003;Vander Zanden et al 2004;Maezono et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Morphologically, as the catfish grows, both its gape size and number of gill rakes increase, conferring more efficiency to filter feeding (Munro 1967). Therefore the trophic impacts of the catfish may be contrary to those of piscivorous invaders, such as different bass and trout species, that cause significant top-down effects within the invaded communities (Flecker and Townsend 1994;Gratwicke and Marshall 2001;Cambray 2003b;Nystrom and McIntosh 2003;Vander Zanden et al 2004;Maezono et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In experimental channels, Nyström and McIntosh (2003) found that trout had a significantly higher effect on invertebrates following sub-catastrophic disturbance compared to undisturbed channels, and this resulted in a progressive decline in invertebrate densities (and commensurate increase in periphyton biomass) during the post-disturbance resilience phase. The mechanism for this was by direct consumption of invertebrates and increased emigration (to avoid predation) by the 'weedy' colonists arriving in the disturbed channels.…”
Section: Hydrological-scale Flow Fluctuations: Daysmentioning
confidence: 95%
“…Freshwater fishes are among the most widely introduced vertebrate group worldwide, and represent the one of the best-studied indicators of invasion impacts (Rahel, 2002;Leprieur et al, 2008;Strayer, 2010). Non-native fishes have disrupted the biota of their recipient ecosystems directly through predation and competition, and indirectly by altering the behaviour and abundance of prey, and disturbing food-web interrelationships (Flecker & Townsend, 1994;Nyström & McIntosh, 2003;Baxter et al, 2004). The general theory of invasion disturbances posits that impacts are often a consequence of cumulative effects related to the distribution range of invaders, their relative abundances within that range, and their per capita effects on individuals, populations and communities of native species (Parker et al, 1999;Dunham et al, 2002;Young et al, 2010;Kadye & Booth, 2012).…”
Section: Introductionmentioning
confidence: 99%